Does surgical or medical management of extrahepatic portosystemic shunts in dogs carry a better prognosis for the resolution and reduction of neurological dysfunction? - Smachlo, Julia; Gordon-Evans, Wanda (Veterinary Evidence, 2022)
PICO question In dogs with congenital extrahepatic portosystemic shunts that are treated with surgical attenuation what is the persistency, frequency, severity and outcome of neurological signs when compared to dogs that are treated medically? Clinical bottom line Category of research question Prognosis The number and type of study designs reviewed Ten papers were critically reviewed Strength of evidence Weak Outcomes reported For short-term success, owners reported an overall decrease in neurological signs associated with neurological dysfunction and an increase in quality of life after the initiation of either medical management or surgical management. Surgical management has a weak association with higher mortality or severe neurological signs in the immediate postoperative period Conclusion It is challenging to make a direct comparison between medical and surgical management but, overall, both strategies seemed to decrease neurological signs in the short term. There was a lack of evidence and available data about the efficacy of each for long-term control of neurological signs How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.